The influence of voltage unsymmetry on the energy characteristics of manure removal conveyors - Sinyavsky, O.; Savchenko, V.; Bunko, V.; Svirida, M. (Energy and Automation, 2023)
It was established that the greatest impact on electric drives of production machines and mechanisms has deviations and asymmetry of the voltage. Voltage asymmetry leads to losses that have an electromagnetic and technological component. Studies of the influence of voltage asymmetry on the technological characteristics of working machines and mechanisms have shown that their productivity decreases with voltage asymmetry. However, there are no studies on the influence of voltage asymmetry on the energy characteristics of working machines. The purpose of the study is to determine the influence of voltage asymmetry on the energy characteristics of manure removal conveyors. When the voltage is asymmetric, the constant and variable power losses in the asynchronous electric motor of manure removal conveyors change, which affects their energy characteristics. It is proposed to carry out an energy assessment of the electric drive of the manure removal conveyor based on the specific consumption of electricity. A study of the effect of voltage asymmetry on the energy characteristics of manure removal conveyors was conducted. The dependence of the specific power consumption on the change in stiffness of the mechanical characteristics of the electric motor, which is caused by voltage asymmetry, is obtained. Since the stiffness of the mechanical characteristics of the asynchronous motor decreases with voltage asymmetry, slippage and power losses increase. As a result, specific losses of electricity in the electric drive of manure removal conveyors increase. Key words: manure removal conveyors, voltage asymmetry, power, conveyor performance, specific power consumption